"Tell Me What You Don't Remember": Care-Seeking Facilitators and Barriers in the Decade Following Repetitive Blast Exposure Among Army Combat Veterans. Issue 2 (1st February 2016) - Chase, Rachel P.; McMahon, Shannon A.; Winch, Peter J.
ABSTRACT: Objectives: This study sought to understand facilitators and barriers to care seeking among blast-exposed veterans and service members who served before the implementation of systematic screening for traumatic brain injury. Methods: Informed by principles of Grounded Theory, we used theoretical sampling and conducted 31 interviews with 15 veterans and 10 veteran family members. Data were iteratively collected and thematically analyzed. Results: The most critical facilitator in initiating care was encouragement—verging on insistence—from a spouse, family member, or employer. Although respondents overwhelmingly described veteran and military health systems responding inadequately to patient needs, respondents also described exceptional health professionals who stood in contrast, dedicated to providing quality care. Barriers to ongoing care included: scheduling complications; redeployments; insufficient or inaccessible documentation of blast encounters or medical history; high provider turnover interrupting therapeutic progress; and poor patient–provider relationships. Respondents described providers as generally dismissive of or insensitive to many health needs. Respondents feared the system was incapable of helping them and described stigma against mental health care seeking in personal and professional spheres. Conclusions: Veterans and their families struggle to address multiple, confusing transformations after repetitive blast exposures. Complex, impersonal, and skeptical health system processes place an undue burden on care-seeking veterans and service members.